Rattus fuscipes Waterhouse 1839 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Rattus fuscipes Waterhouse, 1839. Zool. Voy. H.M.S. “Beagle," Mammalia, p. 66. TYPE LOCALITY: Australia, Western Australia, King George's Sound. DISTRIBUTION: E. Queensland; E. New South Wales; Victoria; South Australia; S.W. Western Australia. COMMENT: Includes assimilis, glauerti, greyi, and manicatus; see Taylor and Horner, 1973, Bull. Am. Mus. Nat. Hist., 150 (l): 15. Reviewed by Musser, 1981, Bull. Am. Mus. Nat. Hist., 169(2): 123. ISIS NUMBER: 5301410011058045001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 5), pp. 504-560 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 549, DOI: 10.5281/zenodo.7353037